Oleanolic Acid Inhibits Liver X Receptor Alpha and Pregnane X Receptor to Attenuate Ligand-Induced Lipogenesis - Lin, Yen-Ning; Chang, Hsiao-Yun; Wang, Charles C. N; Chu, Fang-Yi; Shen, Hsin-Yi; Chen, Chao-Jung; Lim, Yun-Ping (Journal of agricultural and food chemistry, 2018)
Liver X receptor α (LXRα) controls important biological and pathophysiological processes such as lipid homeostasis. Inhibiting LXRα transactivation may beneficial in the treatment of nonalcoholic fatty liver disease (NAFLD), which is one of the main causes of liver diseases and hyperlipidemia. Oleanolic acid (OA) is a naturally occurring triterpenoid found in many plants. It has several beneficial effects on biological pathways; however, the mechanisms underlying its effects on LXRα are unclear. Therefore, we evaluated the effects of OA on T0901317-induced LXRα activation and explored whether OA can attenuate hepatic lipogenesis. The results showed that OA significantly decreased the promoter activities of LXR response element and sterol regulatory element binding protein-1c (SREBP-1c). It also decreased the mRNA and protein expression of LXRα target genes. These resulted in reduced hepatocellular lipid content. Our results also revealed that the overall binding pose of OA is similar to the X-ray pose of T0901317. Furthermore, OA stimulated AMP-activated protein kinase phosphorylation in hepatic cells. Additionally, it increased small heterodimer partner-interacting leucine zipper protein (SMILE) but decreased steroid receptor coactivator-1 (SRC-1) recruitment to the SREBP-1c promoter region. OA also enhanced LXRα-mediated induction of reverse cholesterol transport (RCT)-related gene, ATP-binding cassette transporter (ABC) A1, and ABCG1 expression in intestinal cells. It was found that OA increased the binding of SRC-1 but decreased SMILE recruitment to the ABCG1 gene promoter region. Furthermore, it reduced valproate- and rifampin-induced LXRα- and pregnane X receptor-mediated lipogenesis, respectively, which indicates its potential benefit in treating drug-induced hepatic steatosis. The results also show that OA is liver-specific and can be selectively repressed of lipogenesis. Moreover, it preserves and enhances LXRα-induced RCT stimulation. The results show that OA may be a promising treatment for NAFLD. Additionally, it can be used in the development of LXRα agonists to prevent atherosclerosis.